O contrato de gestão como um instrumento de modernização do estado - Andrade, Nilma Maria de (1995)
This study discusses the contract management implementing process in Brazilian Public Administration and particularly, the experience of the State of São Paulo, that began in 1991. The main objective of contract management is to concentrate the governmental control on the organizations' outcomes, with the gradual simplification of the control structures and the implementation of sanction and reward system. This system can make possible the adoption of new performance evaluation forms and can contribute to improve the Public Sector productivity. The contract management is an instrument which promotes the dialogue and partnership, facilitating the transparency on intentions and orientations between partners. In addition to, it operates as an instrument of administrative rationalization and internai communication for the institution. previous planning system is one of the preconditions to the success of contract management implementing process. The goals and objectives must be specified clearly and without ambiguity, and must reflect the organization reality. Some problems will be avoided with previous training stage, to teach the required skills and concepts, to the technicians that are in charge of the contracfs follow up and implementation. The agreement of key decision makers and leaders about the contract management is essential too. Finally, the work force has to be prepared and conscious about the whole process.